Effect of Silt Size, Concentration on Erosion of Turgo Turbine Blades - Khurana, Sourabh; Goel, Varun; Kumar, Khushmeet; Sethi, Muneesh (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
An experimental investigation in actual flow conditions has been carried out to study the effect of silt size, concentration, jet velocity, operating hours and nozzle angle on erosive wear of Turgo impulse turbine blades. Experiments have shown that maximum erosion occurs at nozzle angle of 20ο for silt size 370 μm and silt concentration of 12000 ppm. During the experiments it has been observed that erosive wear depends on silt size, silt concentration, nozzle angle and operating hours of turbine. A correlation has also been developed as a function of silt size, silt concentration, operating hours of turbine and nozzle angle. DOI: http://dx.doi.org/10.3126/hn.v13i0.10060 HYDRO NEPAL Journal of Water, Energy and Environment Issue No.13, July 2013 Page: Uploaded Date: 03-14-2014